The fallacy of the revised Bretton Woods hypothesis: Why today's international financial system is unsustainable - Thomas I. Palley (Levy Economics Institute of Bard College, 2006)
The stability of the international financial system is in doubt. Analysis of the system has focused mainly on the sustainability of financing the American trade deficit and has failed to understand the microeconomics of transactions within the system. According to this brief by Thomas I. Palley, the international financial system is unsustainable for reasons of demand, not supply. He recommends a global system of managed exchange rates to replace the current system before it crashes, along with the US economy. East Asian economies are pursuing export-led growth and running huge trade surpluses with the United States by actively pursuing policies aimed at maintaining undervalued exchange rates. Their governments continue to accumulate US financial assets in order to support and stabilize the international financial system.While East Asian policymakers are correct in their belief that they can improve economic outcomes through exchange rate intervention, the system is undermining the structure of income and aggregate demand and eroding US manufacturing capacity.
Keywords: 330; Internationales Währungssystem; Internationaler Finanzmarkt; Bretton-Woods-System; Vergleich; Auslandsverschuldung; Kapitalmobilität; Wechselkurssystem